2019
DOI: 10.1002/mgg3.563
|View full text |Cite
|
Sign up to set email alerts
|

IL‐4 gene polymorphisms and their relation to steroid‐induced osteonecrosis of the femoral head in Chinese population

Abstract: Background Steroid‐induced osteonecrosis of the femoral head (ONFH) is a debilitating disease characterized by the activation and infiltration of macrophages into the necrotic site. Interleukin‐4 ( IL‐4 ) administration helped reduce the infiltration of M1 phenotypic macrophages and maintain the activation of M2 phenotypic macrophages, resulting in restriction of inflammation and decrease in osteocyte apoptosis. The aim of this study was to investigate the associations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…56 However, the SNP g.8455A>G rs2243289 of the IL-4 gene was associated with decreased risk of developing steroid-induced osteonecrosis of femoral head in Chinese population. 57 In current study, this SNP g.8455A>G was found in two confirmed positive patients of GI nematode infection who had severe signs and symptoms of disease, but association of this SNP in causing susceptibility to nematode infections cannot be done yet as more comprehensive case control study with large number of case and control samples should be conducted to confirm its association with nematode infections.…”
Section: Discussionmentioning
confidence: 69%
“…56 However, the SNP g.8455A>G rs2243289 of the IL-4 gene was associated with decreased risk of developing steroid-induced osteonecrosis of femoral head in Chinese population. 57 In current study, this SNP g.8455A>G was found in two confirmed positive patients of GI nematode infection who had severe signs and symptoms of disease, but association of this SNP in causing susceptibility to nematode infections cannot be done yet as more comprehensive case control study with large number of case and control samples should be conducted to confirm its association with nematode infections.…”
Section: Discussionmentioning
confidence: 69%
“…We also found a correlation between IL-4 /GTT haplotype composed of rs2243283, rs2243250, rs2243248 and lower AD risk. As reported, rs2243283 gene variants have been confirmed to correlate to some chronic inflammatory and immune diseases, such as asthma, chronic periodontitis, and autoimmune hepatitis ( 22 ). However, as we know, rare studies focused on the linkage of this SNP with AD.…”
Section: Discussionmentioning
confidence: 82%
“…Bradley and his colleagues’ studies showed that the inflammatory infiltrate in SONFH patients comprised primarily CD4(+) T cells and CD68(+) macrophages, the latter of which expressed increased levels of cellular adhesion molecules [ 40 ]. Tianbo et al suggested that polymorphisms of Interleukin-4 (IL-4) gene might be associated with susceptibility to SONFH, which helped reduce the infiltration of M1 phenotypic macrophages and maintain the activation of M2 phenotypic macrophages [ 41 ]. Mayu et al found that neutrophil extracellular traps-forming neutrophils were present in small vessels surrounding the femoral head of patients with ONFH but not osteoarthritis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%